2022
DOI: 10.1001/jamanetworkopen.2022.46299
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Quality Care Among Adults With Rheumatoid Arthritis

Abstract: ImportanceAlthough quality care markers exist for patients with rheumatoid arthritis (RA), the predictors of meeting these markers are unclear.ObjectiveTo explore factors associated with quality care among patients with RA.Design, Setting, and ParticipantsA retrospective cohort study using insurance claims from 2009 to 2017 was conducted, and 6 sequential logistic regression models were built to evaluate quality care markers. Quality care markers were measured at 1 year post-RA diagnosis for each patient. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…38 However, a recent study found quality of care for RA remains variable, especially for patients with Medicare and those with multiple morbidities. 14 As the ACA matured and increased patient access to health care, it is possible that the previously sharply decreasing rate of surgical intervention for RA of the hand abated due to an increase in patients with poorly treated RA interacting with hand surgeons and being candidates for surgery based on existing guidelines. As RA surgical care remains largely elective, shared decision-making continues to be a crucial aspect of patient care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 However, a recent study found quality of care for RA remains variable, especially for patients with Medicare and those with multiple morbidities. 14 As the ACA matured and increased patient access to health care, it is possible that the previously sharply decreasing rate of surgical intervention for RA of the hand abated due to an increase in patients with poorly treated RA interacting with hand surgeons and being candidates for surgery based on existing guidelines. As RA surgical care remains largely elective, shared decision-making continues to be a crucial aspect of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Oversight committees, such as the Arthritis Foundation (a national organization for RA), are taking steps to standardize care through publishing quality care measures . However, a recent study found quality of care for RA remains variable, especially for patients with Medicare and those with multiple morbidities . As the ACA matured and increased patient access to health care, it is possible that the previously sharply decreasing rate of surgical intervention for RA of the hand abated due to an increase in patients with poorly treated RA interacting with hand surgeons and being candidates for surgery based on existing guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical management of different patient groups has lately received attention for other hand surgical conditions and affects health care quality and equality 21 , 22 . A delay in diagnosis and treatment of UNE may decrease the likelihood of full recovery due to the risk of remaining injuries to the nerve trunk, particularly the nerve fibers, i.e., both the axons and the Schwann cells, even after the surgery 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on a large retrospective cohort study of patients with rheumatoid arthritis (RA), researchers report that patients who were male, had Medicare insurance, or had increased comorbidities were generally less likely to meet selected RA quality care markers. (See Seyferth et al, 2022. )…”
mentioning
confidence: 99%